2021
DOI: 10.1200/jco.2021.39.6_suppl.288
|View full text |Cite
|
Sign up to set email alerts
|

Treatment sequence after first-line nivolumab plus ipilimumab or sunitinib monotherapy in patients with metastatic renal cell carcinoma (mRCC) using real-world data.

Abstract: 288 Background: The introduction of second-line (2L) nivolumab (NIVO) in 2015 (CheckMate 025) and first-line (1L) NIVO plus ipilimumab (NIVO+IPI) in 2018 (CheckMate 214) revolutionized the management of mRCC in the US. This study sought to leverage real-world (RW) data by applying CheckMate 214 inclusion criteria to develop a RW comparator for the trial to assess treatment patterns and sequences in RW patients (pts) with mRCC after receiving 1L NIVO+IPI or sunitinib (SUN). Methods: This retrospective study id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
2
1
0
Order By: Relevance
“…Consistent with the study by Zakharia et al [17] , we observed a marked increase in the uptake of both pembrolizumab + axitinib and ipilimumab + nivolumab combinations since their respective FDA approval. In our study, consistent with the literature [18] , [19] , [20] , [21] , 2L therapies were guided by 1L therapies: patients received TKI monotherapy after IO-based 1L treatment, and received an IO-based therapy after TKI-based 1L treatment. Cabozantinib was the most common 2L therapy among patients receiving IO-based 1L therapy, and nivolumab was the most common 2L therapy among patients receiving 1L TKI monotherapy.…”
Section: Discussionsupporting
confidence: 82%
“…Consistent with the study by Zakharia et al [17] , we observed a marked increase in the uptake of both pembrolizumab + axitinib and ipilimumab + nivolumab combinations since their respective FDA approval. In our study, consistent with the literature [18] , [19] , [20] , [21] , 2L therapies were guided by 1L therapies: patients received TKI monotherapy after IO-based 1L treatment, and received an IO-based therapy after TKI-based 1L treatment. Cabozantinib was the most common 2L therapy among patients receiving IO-based 1L therapy, and nivolumab was the most common 2L therapy among patients receiving 1L TKI monotherapy.…”
Section: Discussionsupporting
confidence: 82%
“…We observed a trend toward an increasing use of ipilimumab plus nivolumab and pembrolizumab plus axitinib after the FDA approval. Literatures reported that second-line therapies are affected by the first-line treatments:patients received TKIs after IO-based therapies; patients received IO-based therapiesafterTKIs treatment [11,13,14]. The present study also observed a similar finding: for patients receiving ipilimumab plus nivolumabor pembrolizumab plus axitinib as first-line therapy, the most common second-line treatment was cabozantinib (54.6%).…”
Section: Discussionsupporting
confidence: 83%
“…Several phase III clinical trials demonstrated the efficacy of such combination therapies, including CheckMate 214 (Ipilimumab + Nivolumab versus Sunitinib), KEYNOTE-426 (axitinib + pembrolizumab versus sunitinib),CHECKMATE-9ER (cabozantinib + nivolumab versus sunitinib), CLEAR (pembrolizumab + lenvatinib versus sunitinib), and JAVELINtrial (avelumab + axitinib versus sunitinib) [2][3][4][5][6][7]. However, only a few studies reported real-world data regarding treatment pattern and clinical outcome of combination therapies on RCC [11][12][13][14]. In this era of IO and TKI targeted therapy, it is important to understand the treatment efficacy and sequence of these agents.…”
Section: Introductionmentioning
confidence: 99%